Parent-Infant Interactions Among Infants With High Risk of Cerebral Palsy: A Protocol for an Observational Study of Infant and Parental Factors for Dyadic Reciprocity - Røhder, Katrine; Willerslev-Olsen, Maria; Nielsen, Jens Bo; Greisen, Gorm; Harder, Susanne (Frontiers in Psychiatry, 2021)
Background: An early diagnosis of chronic disability, such as risk of Cerebral Palsy (CP), is likely to affect the quality of parent-infant interactions by affecting both infant and parental factors. Due to adverse perinatal events, infants at high risk of CP may exhibit less engagement in interactions, while parents may experience increased mental health problems and disrupted parental representations that can have a negative effect on parental sensitivity. Recent clinical guidelines on early intervention among families with infants at risk of CP recommends supporting parental sensitivity and mutual enjoyable interactions but more research is need to inform such interventions. This includes understanding how infant and parental risk as well as resilience factors impact parent-infant interactions and how existing parenting programs developed among typical developing infants should be adapted to families with infants at risk of CP. In addition, as majority of research on infant neurohabilitation focus on improving motor and cognitive outcomes research on infant emotional development is needed. The study aim is to assess the quality of early parent-infant interactions in families with high-risk infants, compared to families with low-risk infants, and to explore how interaction quality is affected by infant and parental factors. Three potential mediating factors explaining the association between CP risk and less optimal parent-infant interactions will be explored: infant interactional capacities, parental mental health and wellbeing, and parents’ representations of their child. Methods: The prospective, longitudinal design will follow infants at high risk for CP and their parents and a control group at three time points from 15 weeks to 15 months corrected infant age (CA). Measures comprise infant developmental assessments, questionnaires and interviews with both parents, and global ratings of video-recorded parent-infant interactions. Discussion: Study results will enhance our understanding of how parent-infant interactions may be affected by perinatal neurological risk and identify potential important mechanisms for observed associations. This knowledge could assist in planning future early screening and intervention programs and identifying families who should be offered targeted psychological interventions in addition to neurohabilitation programs.